2009
DOI: 10.1017/s0022215109990764
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial hypertension secondary to sigmoid sinus compression by group A streptococcal epidural abscess

Abstract: This is the first reported case of intracranial hypertension due to an epidural abscess causing sigmoid sinus compression without thrombosis. This case illustrates the fact that, even in the absence of thrombosis of the sigmoid sinus, a small epidural abscess may require urgent surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
(8 reference statements)
0
2
0
Order By: Relevance
“… 39 Epidural abscesses can also restrict venous outflow. 40 Of note, while lesion volume can appear small (see Figure 4(b) ), the impact on ICP may be wholly unrelated and excessive (compared to the apparent reserve space/compliance of a CT image).…”
Section: Introductionmentioning
confidence: 99%
“… 39 Epidural abscesses can also restrict venous outflow. 40 Of note, while lesion volume can appear small (see Figure 4(b) ), the impact on ICP may be wholly unrelated and excessive (compared to the apparent reserve space/compliance of a CT image).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the management of venous sinus thrombosis, a previous report has shown that tympanostomy tube insertionor myringotomy aloneis usually sufficient surgical therapy (in addition to IV antibiotics and consideration of anticoagulation therapy) [11]. In this case, a cortical mastoidectomy, or perhaps even more extensive surgery, would have been considered had there been evidence of coalescence, cholesteatoma and/or an abscess adjacent to the venous sinus thrombosis [12].…”
Section: Discussionmentioning
confidence: 99%